Efektivitas Pengelolaan Hutan Kemasyarakatan Pada Berbagai Strata Luasan Lahan Di Kawasan Hutan Sesaot Lombok Barat: The Effectiveness of Community Forest Management in Various Strats of Land Area in the Sesaot Forest Area of West Lombok - Markum Markum; Andi C Ichsan; Husni Idris (LPPM Universitas Mataram, 2023)
What is the exact area of community forestry (HKm) land that can be effectively managed by farmers? The objectives of the study were 1) to identify HKm land management practices by farmers based on vegetation density and income at various strata of land area, 2) to analyze the effectiveness of HKm land management in various strata of land area, 3) to analyze the factors that influence the effectiveness of land management in various strata. strata of land area The method used in this research is descriptive through a series of observations, interviews and Focus Group Discussions. The number of respondents interviewed was 42 people. The variables studied included environmental aspects such as plant density, economic aspects in the form of production values and effectiveness assessment using scoring techniques, with the decision criteria being very effective, effective, quite effective, less effective and ineffective. Based on the results of the study, it can be concluded that (1) plant density in various land strata in strata I (<0.25 ha), strata II (0.25-0.5), strata III (>0.5-1ha) and Strata III (>0.5-1ha). IV(> 1 ha) were 382, 387,389 and 378 plants/ha, respectively. Meanwhile, the income of each farmer is (Rp/ha/year): 46,494,744; 25,479,880; 39,704,174 and 31,358,023. From various land strata, the level of effectiveness of the management is categorized as effective for land strata I, III, and IV and quite effective for land strata II. The factor that influences the effectiveness of land management is land area, where there is a tendency that the smaller the land area, the more effective the management. Other factors are the application of agroforestry patterns, other land tenure, availability of labor and age of farmers. Suggestions put forward for land distribution policies should consider the area between 0.5 - 1 ha, because it has provided sufficient income for farmers.